Thermal Catalytic Production of Potassium Humate Fertilizer from Tobacco Straw and Its Performance in Wheat Hydroponics - Qianqian, Li; Jinlin, Li; Yinqiao, Zhao; Yingjie, Zhu; Baikenov, M.I.; Xiaofei, Liu; Xintai, Su (Karagandy University of the name of acad. E.A. Buketov, 2024)
Production of artificial humic acid (AHA) from waste biomass will contribute to environmental protection and agricultural productivity. However, there is still a lack of a faster, more efficient and eco-friendly way for sustainable production. In this study, potassium humate was prepared from agricultural waste tobacco straw by thermal catalysis using environmentally friendly Fe2O3 as a catalyst. The yield of potassium humate was successfully increased to 68.77 %. In the present study, using characterization methods such as TG-DTG and UV, it was found that the potassium humate prepared from tobacco straw had lower aromaticity, smaller molecular weight, as well as better solubility and better quality. In addition, the effect of potassium humate fertilizer on wheat biomass was also investigated in this experiment by wheat hydroponics. The results showed that the germination rate of wheat increased by 17 % and the fresh and dry weights increased by 6.94 % and 19.31 %, respectively, with the addition of potassium humate prepared with iron catalyst. This study provides a green and simple technology for the resourceful utilization of tobacco straw to produce high value-added potassium humate, and enriches the source of raw materials for potassium humate, expanding its application in the field of crop growth.
Keywords: Tobacco straw; potassium humate; wheat growth; wheat hydroponics; artificial humic acid (AHA); biomass; tobacco straw; thermal catalysis; fertilizer